Citizenship into Practice in England: The Continuing Professional Development Challenge (Estudios sobre Educación, 2006)
This paper surveys the strategies adopted in England to support the development of teachers’ subject knowledge and confidence in relation to teaching Citizenship, which was introduced as a new statutory subject in the National Curriculum in 2002. It reviews examples of good practice and explores how a continuing professional development (CPD) strategy developed at several levels to support teachers and curriculum managers. It outlines the challenges and obstacles in relation to implementing effective Citizenship education in schools. It also underlines the fundamental importance of Citizenship education if young people are to understand and engage with contemporary events in the early Twenty First Century.